1995
DOI: 10.1121/1.414374
|View full text |Cite
|
Sign up to set email alerts
|

Hot spots in the newborn vowel space

Abstract: The vowels /i/, /y/, /u/, and /unrounded u/ define one surface of the vowel space, whether defined in articulatory or acoustic terms. Adults can give goodness ratings to vowels from the space surrounding prototypic vowels, the prototypic vowels typically obtaining the highest ratings. Does this reflect unlearned structural sensitivities or some averaging process during life? Is it true in newborns? Attractiveness or ‘‘goodness’’ was measured by how long newborns listened to first presentation of a set of vowel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These studies have presented subjects with extended passages of speech. Aldridge (1995Aldridge ( , 1997Aldridge, Stillman & Bower, 1999) presented infants with individual vowel sounds. It was found that newborns showed a hierarchy of preference for vowel sounds, with the vowels aia and aua being preferred over the vowelaya, which was preferred over the vowel aÀa.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have presented subjects with extended passages of speech. Aldridge (1995Aldridge ( , 1997Aldridge, Stillman & Bower, 1999) presented infants with individual vowel sounds. It was found that newborns showed a hierarchy of preference for vowel sounds, with the vowels aia and aua being preferred over the vowelaya, which was preferred over the vowel aÀa.…”
mentioning
confidence: 99%
“…The alternative explanation was pointed out by members of the audience atAldridge (1995). The alternative explanation was also sent by e-mail.…”
mentioning
confidence: 99%